Profiling Darkweb Child Sexual Exploitation Material Forum Members Using Longitudinal Posting History Data. (August 2022) - van der Bruggen, Madeleine; Blokland, Arjan
Darkweb fora dedicated to the illegal exchange of child sexual exploitation material (CSEM) continue to thrive. Profiling forum members based on their communication patterns will increase our insights in the dynamics of online CSEM and may aid law enforcement to identify those members who are most influential and pose the highest risk. The current study uses data from a large English language Darkweb CSEM forum that was active between 2010 and 2014, containing over 400, 000 posts. Posts were time stamped, categorized based on subforum topic, and linked to individual forum members by nickname. Group-based trajectory modeling was subsequently applied to derive forum member profiles based on members' posting history. Analyses show that over the course of the observation period, overall activity levels—in terms of total number of posting members and the average number of posts per month per member—fluctuate substantially and that multiple developmental pathways—in terms of monthly patterns in the frequency of posts by individual members—can be distinguished. Theoretical and practical ramifications of these findings are discussed.